An Extreme Heat Event Induced by Typhoon Lekima (2019) and Its Contributing Factors. Issue 11 (27th May 2021) - Zhao, Dingchi; Lin, Yanluan; Li, Yuanlong; Gao, Xiaoyu
Abstract: As two prominent natural hazards, tropical cyclone (TC) and heat compound events seem irrelevant on most occasions. TC generally leads to cooling, but could induce extreme heat days (EHD) and heat compound hazard under certain circumstances. An EHD along the southeastern coast of China (SECC) associated with Typhoon Lekima (2019) is documented with its major contributing factors. The formation and intensity of the EHD were found to be closely related to the outer circulation of Lekima by comparing a series of WRF simulations. Via a boundary layer heat budget, we found local sensible heat flux was a necessary, but not sufficient condition for this EHD. Aided by a backward trajectory analysis, we found that upstream surface sensible heat flux, subsidence induced by Typhoon Lekima, and foehn effect due to local topography played approximately equal roles to the occurrence of the EHD. The retreat of regional land‐sea breeze circulation was also beneficial to the appearance of the EHD. Such TC‐heat events might be more overwhelming due to more vigorous TCs with warming in the future. Plain Language Summary: Tropical cyclone (TC) and heat compound events pose a severe threat to human health and natural ecosystems. This paper documents an extreme heat days (EHD) along the southeastern coast of China associated with Typhoon Lekima (2019). Through a series of WRF simulations, we found that the formation and intensity of the EHD are closely related to the outer circulation of Lekima. The local sensible heat flux was necessary, but insufficient for the formation of the EHD. The upstream surface sensible heat flux, subsidence induced by Typhoon Lekima, and foehn effect due to local topography were the key factors to the occurrence of the EHD and the contributions of these three factors were approximately equal. Regional land‐sea breeze circulation influenced by Lekima was also beneficial for the EHD. Such TC‐heat events can be more widespread and severe due to increased intensity of tropical cyclones with warming. Key Points: An extreme heat event along the southeastern coast of China was closely related to the outer circulation of Typhoon Lekima (2019) Upstream surface sensible heat flux, subsidence induced by Typhoon Lekima, and foehn effect due to local topography played approximately equal roles for the event Retreat of regional land‐sea breeze circulation also favored the event